Makna Simbolik Rajam Dan Sorban Sebagai Representasi Kekuasaan Patriaki Dalam Dua Film Lintas Budaya Kontemporer - Wulandari Wulandari; Siti Fatimah Khoeriyah; Siti Aisah; Fatimah Tsalatsa Nur Fitriani (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study explores how patriarchal power is represented in two cross-cultural films: The Stoning of Soraya M. and Perempuan Berkalung Sorban (The Woman with the Turban). The main focus lies on the symbolic roles of stoning and the turban as tools of female oppression. Stoning is depicted as a harsh and permanent form of patriarchal control, legitimized through religious interpretations in the context of Iranian society. In contrast, the turban serves as a symbol of ideological dominance within the pesantren (Islamic boarding school) structure in Indonesia, subtly reinforcing gender hierarchy through education and religious narratives. Utilizing a qualitative descriptive approach and comparative literary analysis, this study reveals that both symbols—despite differing in form and intensity—function as mechanisms for legitimizing male authority: one through acts of violence, the other through the internalization of doctrine. The female characters in both films demonstrate resistance using different strategies: Soraya through symbolic defiance within an oppressive theocratic society, and Annisa through active rebellion via education and intellectual freedom. This analysis contributes a fresh perspective to feminist film studies by highlighting the role of cultural symbols in either sustaining or challenging gender-based oppression. Moreover, the study encourages a critical re-evaluation of religious and cultural interpretations that uphold patriarchal systems, offering deeper insight for broader feminist discourse and social transformation through visual media.